Professorial evaluation of the teaching-learning process of the discipline of Pharmacology in an Angolan university - Bange Cassenda Fernando, Fernando; Fernandes, Ana; Chipango, Agostinho; Lardoeyt Ferrer, Roberto (Spanish Journal of Medical Education, 2024)
Background: The discipline of Pharmacology is taught in the fifth and sixth semesters with a load of 64 hours respectively in the university degree program in pharmaceutical sciences at the Jean Piaget Higher Polytechnic Institute of Benguela. Objective: to characterize the teachers’ perception of the teachinglearning process (TLP) of the discipline of Pharmacology. Methods: A crosssectional descriptive observational study was carried out in which a questionnaire with four dimensions and 25 variables was applied to the universe of teachers of the subjects of Pharmacology and Clinical Pharmacy. Results: On the planning and direction of the TLP of Pharmacology; sometimes the program and other official documents allow the teacher to be guided (100%). About the didactic orientation of the content; 85.7% of teachers gave an unfavorable response. In relation to the planning and direction of experimental activities as part of the resolution of a problem; 71.4% of teachers reported an unfavorable state of opinion regarding the preparation of teaching tasks promoting the use of ICTs. On the professional and scientificmethodological nature of the TLP; sometimes different forms of teaching organization are conceived (57.1%). About student learning; the development of students’ skills in terms of learning is regular (100%). Conclusions: the development of the current TLP in the discipline of Pharmacology does not guarantee the acquisition of knowledge, skills and values, which enable the future professional performance of the graduate.